Initial oxidation of sulfide sites on a galena surface: Experimental confirmation of an ab-initio calculation - Eggleston, Carrick M. (Geochimica et cosmochimica acta, 1997)
Mechanisms of sulfide mineral oxidation have been a subject of long-standing interest because of their importance in many industrial, geochemical and environmental processes. Atomic-esolution scanning tunneling microscopy (STM) has been applied to sulfide mineral oxidation, but interpretation of the results has been limited by a lack of independent electronic structure information. Becker and Hochella (1996) recently published ab-initio quantum calculations for galena (PbS) surfaces, predicting that for oxidation of S sites by atomic or molecular oxygen, oxidized sites should appear dark in STM images of occupied states, but bright in images of unoccupied states. This is because oxidation draws charge away from S atoms, thus creating a greater density of STM-imageable unoccupied states. This Scientific Comment reports experimental evidence in support of their calculation. Dual-bias STM imaging shows a few apparently oxidized dark sites in an occupied-states image, and bright sites in these locations in an unoccupied-states image, suggesting that the structures assumed by Becker and Hochella (1996) for calculation purposes are valid.